1983
DOI: 10.1111/j.1464-410x.1983.tb03410.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Optical Urethrotomy on the Management of Urethral Strictures

Abstract: The introduction of optical urethrotomy by Sachse has reduced the need for urethroplasty: 261 urethroplasties were performed between 1964 and 1983, of which 87 were performed in one stage on patients who would today have undergone urethrotomy as the procedure of first choice. The results in this group are compared with those in 151 patients treated between 1978 and 1983 by 265 internal optical urethrotomies. At 5 years 50% of those treated by urethrotomy needed no further treatment, compared with 83% of those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
2
5

Year Published

1986
1986
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 4 publications
1
23
2
5
Order By: Relevance
“…The idiopathic etiology of stricture in our study was idiopathic in 39.13% followed by traumatic injuries in 26% cases. In contrast to our study Chelton et al [10] reported 11.5% traumatic stricture. The high incidence of traumatic stricture in our study was due to road traffic accidents & war injuries.…”
Section: Discussioncontrasting
confidence: 99%
“…The idiopathic etiology of stricture in our study was idiopathic in 39.13% followed by traumatic injuries in 26% cases. In contrast to our study Chelton et al [10] reported 11.5% traumatic stricture. The high incidence of traumatic stricture in our study was due to road traffic accidents & war injuries.…”
Section: Discussioncontrasting
confidence: 99%
“…In 1983, Chilton et al [11] treated all but 5% of 261 patients endoscopically for urethral stenosis, although even then there were already reports of numerous series in which cure rates were 80-95% with end-to-end anastomosis [12]. In 1993 Mundy [13] noted that most urethral strictures were still treated by urethrotomy and/or dilatation, and asserted that urethroplasty had a minor role, being indicated only in patients with particularly complex strictures, or in whom previous treatments had failed.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple strictures were found in 7% of cases. Various other studies have also reported bulbar urethra being the commonest site of urethral stricture [10,11]. In the present study 80% of the cases had short strictures i.e., stricture length was less than 2 cms.…”
Section: Discussionmentioning
confidence: 49%